PKM Community Empowerment through Cultivation of Rosella Flowers in Ban Village, Kubu District, Karangasem - Wirajaya, Anak Agung Ngurah Mayun; Azmi, Aida Firdaus Muhammad Nurul; Udayana, I Gusti Bagus; Mahardika, Ida Bagus Komang; Sudewa, Ketut Agung; Yuliartini, Made Sri; Arjana, I Gusti Made; Muliarta, I Nengah; Sukmadewi, Desak Ketut Tristiana; Apriliathi, Ni Putu Siska; Rahayu, Ni Ketut Sri; Suastyayama, Kadek Damana (Asian Journal of Community Services, 2024)
Ban Village is a village located in Kubu District, Karangasem Regency. Most of the people's livelihoods are farmers, breeders and coffee processors. Despite its shortcomings in terms of land conditions, Ban Village has a variety of natural potential that needs to be developed in the agricultural, livestock, fishery and crop processing sectors. The potential for re-development of rosella flowers which were cultivated before the Covid-19 pandemic by the community. Cow dung and litter can be used as quality organic fertilizer. The aim of the activity is: increasing the knowledge and skills of partners in cultivating roselle plants and processing cow dung and litter as organic fertilizer and touching on technology for cultivating roselle flowers and processing cow dung and litter.